Successful kindergarten transition your guide to connecting children, families & schools - Pianta, Robert C.; Sayre, Marcia Kraft (Paul H. Brookes, 2003)
"A smooth transition to kindergarten is an essential part of a child's early academic experience - and this guide has the field-tested methods schools need to make this happen. Ideal for preschool and kindergarten teachers, administrators, and family support specialists, Successful Kindergarten Transition introduces a model that has been adopted in diverse schools and communities."--Jacket.